Efficacy of Local Anesthetic: A Narrative Literature Review and Clinical Update in Dentistry - Faisal Kuswandani; Felisha Febriane Balafif; Nuroh Najmi; Anggun Rafisa (Sean Institute, 2023)
Achieving adequate anesthesia in patients is one of the most important aspects of the practice of dentistry to control or eliminate of pain. Pain is one of the most commonly experienced symptoms in dentistry and is a major concern to the dentist. The most essential skill of all dental practitioners is the ability to provide safe and effective local anesthesia. Several local anesthetics are used by the dentist, lidocaine has been considered as the golden standard for local anesthetic agents in dentistry for years. Articaine and mepivacaine both relatively new anesthetic agents are now widely used too. The purpose of this article is to provide a pharmacological profile of the various local anesthetic formulations in current use and their technical considerations.